Skin data from the Visual Sweden project DROID - Lindman, Karin; Rose, Jerónimo F.; Lindvall, Martin; Stadler, Caroline Bivik (AIDA Data Hub, 2019)
The dataset consists of 99 H whole slide skin images (WSI) - 49 abnormal and 50 normal cases. All significant abnormal findings identified are outlined and categorized into 13 types such as actinic keratosis, basal cell carcinoma and dermatofibroma. Other tissue components, such as epidermis, adnexal structures, as well as the surgical margin are delineated to create a complete histological map. In total, 16741 separate annotations have been made to segment the different tissue structures and link them to ontological information.
Keywords: Pathology; Skin; Cancer; Whole slide imaging; Annotated; Cancer and Oncology; Cancer och onkologi; Medical and Health Sciences; Medicin och hälsovetenskap